HOW IS THE IMPLEMENTATION OF ISLAMIC-BASED CHARACTER EDUCATION STRATEGY FOR CHILDREN WITH SPECIAL NEEDS? - Yenni Muflihan; Sri Hartati; Ahmad Arkadius (Journal Informatic, Education and Management (JIEM), 2026)
Implementing Islamic-based character education in inclusive schools presents a challenge, especially for children with special needs who require a specialized approach to achieve their academic and developmental goals. The objectives of this research are to explore the strategies used to implement character education for children with special needs. This study used a qualitative phenomenological approach. Data were collected through in-depth interviews with seven teachers at Harsya Inclusive School. The data were then analyzed using ATLAS.ti 22 software to identify recurring themes and strategies in the implementation of character education. This study identified several strategies for implementing character education, including friendly and communicative, observation, social care, image media, evaluation, independence, therapy, religious values, discipline, communication, patience, rewards, understanding of children, training, sentra, regulation, cooperation with parents, mentoring, habituation, moral value, punishment, repetition, storytelling. The findings indicate that Islamic-based character education in inclusive schools can be implemented effectively through many strategies. This approach not only helps children with special needs achieve their academic goals but also strengthens their social attitudes and moral development. This study provides valuable insights for teachers, parents, and policymakers in designing more comprehensive character education programs in inclusive educational settings.